The rainbow connection number of the enhanced power graph of a finite group - Luis A. Dupont; Daniel G. Mendoza; Miriam Rodriguez (Electronic Journal of Graph Theory and Applications (EJGTA), 2023)
Let G be a finite group. The enhanced power graph ΓGe of G is the graph with vertex set G and two distinct vertices are adjacent if they generate a cyclic subgroup of G. In this article, we calculate the rainbow connection number of ΓGe.